Synthesis of cephradine metal complexes and its anti-bacterial evaluation - Hussain, Iqbal; Syed Salman; Iftikhar, Sarwat; Jan, Samin; Akhter, Junaid; Muhammad Ramzan; Ullah, Atta; Ullah, Riaz; S. Alsaid, Mansour; A. Shahat, Abdelaaty; Syed Hidayathulla (Penerbit Universiti Kebangsaan Malaysia, 2018)
Cephradine belongs to the first generation cephalosporin having a broad range of anti-bacterial activities. In the present work, Cephradine wasreacted with different metal salts. These metal salts were Iron, Copper, Cobalt and Nickel salts. All the complexes of Cephradine metals were synthesized at room temperature using a mechanical vibrator. The reactions yielded the coordinated complexes within 5-10 min with improved product yield. The synthesized complexes were analyzed for their antibacterial power using disc diffused assay. All the Cephradine complexes showed powerful antibacterial activity. The Co, Cu, Ni and Sn complexes showed good antibacterial activities 18.5 mm by Cu complexes against S. typhi, 17 mm against B. subtillus 16.5 mm against S. aureus, 16 mm against S. coccus. Similarly Sn complexes exhibited 17 mm zone of inhibition against S. coccus and 15.5 mm against B. subtillus. Cobalt and Ni complexes also shed significant inhibition activities against bacterial pathogenic bacterial strains. The study is of particular importance and new, using mechanical vibrator for the first time. The product yield is also comparatively good with short reaction time.